A phenomenological study of resident and faculty experiences with learner engagement in the normalization of workplace-based assessment - Mc Donald, Melissa; Muir, Fiona (Canadian Medical Education Journal, 2024)
Background: Workplace-based assessments (WPBA) have become integral to learner-centred medical education. As previous research has linked learner engagement to WPBA implementation, this study explores residents’ and faculty members’ experiences with learner engagement in the normalisation of WPBA practice. Methods: Transcendental phenomenology was used as the qualitative approach, focusing on the participants’ lived experiences. A semi-structured interview guide was used to interview five faculty members and five residents who had conducted WPBA. The interviews were transcribed and analysed using phenomenological data analysis. Results: Three themes were identified between learner engagement and WPBA conduct: (a) work environment, (b) roles and relationships, and (c) mutually beneficial teaching and learning. WPBA learner engagement occurred when participants interacted with each other and with the clinical setting to facilitate teaching and learning. Both participant groups reported a desire to participate in WPBA, but time constraints at times hindered participation. The residents indicated that WPBA improved their knowledge and admitted to experiencing negative emotions during the assessment. Overall, participants recognised the reciprocal benefits of WPBA participation for their professional development. Conclusion: The findings of the study suggest that learner engagement influences the use of WPBA. Consequently, it may be beneficial to consider the role of learner engagement to normalise WPBA application for teaching and learning in the clinical context.